EduBingo: Developing a Content Sample for the One-to-One Classroom by the Content-First Design Approach - Chang, Sung-Bin; Lin, Chi-Jen; Ching, Emily; Cheng, Hercy N. H; Chang, Ben; Chen, Fei-Ching; Wu, Denise; Chan, Tak-Wai (Educational technology & society, 2009)
The successful adoption of technologies in classrooms, we argue, relies on a greater emphasis on content-related pedagogical models for technology enhanced learning design. We propose thecontent-first design, an approach to creating content sample in the one-to-one classroom—classrooms with a wireless enabled computing device available for each student. To demonstrate this design approach, we take arithmetic calculation (fractions, multiplications, divisions, etc.) in elementary schools as the subject domain with EduBingo, an educational game system played in one-to-one classrooms. The system allows the teacher to monitor the accuracy and speed of the student answers during a game session, and the students can reflect on their answers after the game. Two trial tests are described, one focusing on the students while the other on the teacher. The first test indicates that the students make progress on arithmetic fluency from one session to another and that the game promotes positive affect; the second illustrates how a teacher felt the game fit into her classroom practices. This paper emphasizes those considerations that are most vital to the content-first design approach proposed herein.